Exploration of Commonly Used Tests to Assess Physical Qualities in Male, Adolescent Rugby League Players: Discriminative Validity Analyses and Correlations with Match Performance Metrics - Michael A. Carron; Aaron T. Scanlan; Thomas M. Doering (Sports)
Tests assessing physical qualities are regularly used in youth rugby league teams for various functions. However, the utility of such tests is under-explored in this population. In this way, tests are commonly examined in terms of how well they can differentiate performances between groups that are expected to differ and how they relate to outcomes in actual competitive contexts. Therefore, the purpose of this exploratory study was to investigate the discriminative validity and relationships to match performance metrics of frequently used tests to assess physical qualities in male, adolescent rugby league players. Anthropometric (standing height and body mass) and fitness-related (20 m linear sprint, 505-Agility Test, L-run Test, medicine ball throw, countermovement jump, one-repetition maximum back squat, bench press, and prone row tests, and Multistage Fitness Test) physical qualities were measured using common tests in 42 players (16.1 ± 1.3 years). Test outcomes were compared between players in different age and positional groups for discriminative validity analyses. Relationships between test outcomes and match performance metrics gathered via global positioning system and video analysis were also determined. Compared to younger players (14–15 years), older players (16–18 years) had significantly better fitness-related physical qualities (p < 0.05, d = −1.78–1.66), but similar anthropometric qualities (p > 0.05, d = −0.45–0.20). Significant, moderate correlations (p < 0.05, r = 0.56–0.70) were found between (1) one-repetition maximum (1-RM) back squat and relative (per min) high-speed running distance and maximum velocity in matches; (2) 20-m sprint time and relative total distance; (3) 505-Agility Test time and relative line breaks; and (4) height and relative unsuccessful tackles. Consequently, commonly used fitness-related tests demonstrate discriminative validity in detecting differences between age groups, with standing height and the 1-RM back squat showing promising utility given their associations with key match metrics in adolescent rugby league players.